Guinness world records, 2001. (London [England] : Guinness World Records, 2000)
Updates world and American records and reports new categories established during the year.
Includes indexes.
Elem. School Library Collection
Wilson's Junior High School
Young Adult.
Young Adult
Keywords: Curiosities and wonders; Curiosities and wonders; World records; World records